Christianity and criminal law - Hill, Mark; Doe, Norman; Helmholz, Richard H.; Witte, John (Law and Religion Ser., 2020)
This collection, by leading legal scholars, presents historical, theological, philosophical, and legal perspectives on Christianity and Criminal Law. The book will be an invaluable resource for students and academics working in the areas of Law and Religion, Legal Philosophy and Theology.